Rheological Behaviour of the Urea Denatured Soybean Protein (Journal of Fiber Bioengineering and Informatics, 2009)
This paper reports the study of rheological properties of the urea denatured soybean protein in concentrations of 10 % after 0 mol L^{-1} ∼ 10 mol L^{-1} urea treatment using a programmable control revolving viscometer (Brookfield RVDV-II+/SSA-SCL27). A theoretical foundation is provided in this paper to study the exploitation and application of soybean protein. The results show that after urea denaturation the soybean protein solution was a typical pseudoplastic fluid while before it was a Bingham character fluid. The viscosity of both decreased with shear rates and increased with urea contents. The change was much obvious at the urea concentration of 4 mol L^{-1} ∼ 6 mol L^{-1}. After urea denaturation, the non-Newtonian index of soybean protein solution increased from 0.17 to 0.3 ∼ 0.4 at 20°C, which was still fairly low. The stabitily of fluids was pretty bad. The viscosity dropped with temperature significantly.